2010
DOI: 10.1002/cm.20450
|View full text |Cite
|
Sign up to set email alerts
|

Strikingly fast microtubule sliding in bundles formed by Chlamydomonas axonemal dynein

Abstract: Chlamydomonas axonemal extracts containing outer-arm dynein bundle microtubules when added in the absence of ATP. The bundles dissociate after addition of ATP (Haimo et al., Proc Natl Acad Sci USA 76:5759-5768, 1979). In the present study, we investigated the ATP-induced bundle dissociation process using caged ATP. Application of approximately 0.5 mM ATP induced microtubule sliding at approximately 30 microm.s(-1), which was 1.5 times faster than the microtubule sliding observed in protease-treated axonemes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
(65 reference statements)
4
6
0
Order By: Relevance
“…S1, B and C) (7). Evidence from a previous study showed that the microtubule sliding is strikingly fast if OADs are aligned in bundles (8). Besides, our reconstitution assay reveals that ordered OAD arrays can be spontaneously formed in the presence of MTD, in line with a previous finding (6).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…S1, B and C) (7). Evidence from a previous study showed that the microtubule sliding is strikingly fast if OADs are aligned in bundles (8). Besides, our reconstitution assay reveals that ordered OAD arrays can be spontaneously formed in the presence of MTD, in line with a previous finding (6).…”
supporting
confidence: 90%
“…1a and 1b) (25, 26) . Early evidence showed that the microtubule sliding is strikingly fast if OADs are aligned in bundles (27) . Studies also revealed that the sliding could be ceased by blockage of several adjacent OADs, suggesting OADs are successively activated along an MTD (19) .…”
Section: Resultsmentioning
confidence: 99%
“…The velocity was variable (Fig S2B ), with some MTs sliding much faster than those observed in gliding assays. Fast sliding was previously observed with similar dynein-MT complexes but with much higher concentration of dynein, and was interpreted as the effect of cooperation of dyneins aligned with the 24-nm periodicity (Aoyama & Kamiya, 2010).…”
Section: Motile Properties Of the Dynein-mt Complexsupporting
confidence: 66%
“…As reported previously, flagellar outer-arm dynein molecules are aligned on a microtubule in a selforganizing manner with the interval of 24 nm (30,31). Furthermore, the dense cluster of dynein molecules on a microtubule enables the complex to travel a long distance along another microtubule (>10 μm) toward the minus end in the presence of ATP (32,33). For example, ∼40 dynein molecules can be mounted linearly even on 1-μm microtubule fragments and interact with a track microtubule cooperatively.…”
Section: Significancementioning
confidence: 54%